Service Delivery Protests, Struggle for Rights and the Failure of Local Democracy in South Africa and Uganda: Parallels and Divergences - Mbazira, Christopher (South African Journal on Human Rights, 2013)
Although the two countries are thousands of miles apart, Uganda and South Africa have both experienced service delivery protests in recent years. The protests have been directed mainly at local governments, although in Uganda some are directed at private service providers such as the electricity distributor, Umeme. There are a number of parallels and divergences between the two countries, particularly in relation to the causes and the nature that the protests have taken. Both countries are experiencing challenges in implementing decentralisation, which has mainly been characterised by a failure to effectively involve local communities in decision-making as a way of effecting local democracy. Mismanagement, corruption, and incapacity to deliver at the local levels are common to both countries. The divergences relate mainly to the level of organization, frequency and magnitude of the protests. The local government legal framework of Uganda does not emphasize service delivery as much as the South African legal framework does. There is an urgent need for both countries to make local democracy work by building civic competence and creating operational and effective structures for civic participation in local affairs.
Keywords: local government